Ethnic-German Cooperatives in Eastern Europe between the World Wars: The Ideology and Intentions behind an Ethnic Economy - Bernd Robionek (National Economies: Volks-Wirtschaft, Racism and Economy in Europe between the Wars (1918-1939/45), 2015)
Bernd Robionek gives an overview of the development of ethnic-German cooperatives in Eastern Europe between the World Wars and analyses their political and economic role within German national revisionist policies.
Keywords: 330; ethnic economy; cooperatives; ethnic Germans; minority politics; Volksdeutsche; Genossenschaften; Osteuropa; Revisionspolitik